Pelaksanaan Perkuliahan Matematika pada Masa Pembelajaran Jarak Jauh di Jurusan PGSD FKIP Universitas Syiah Kuala - Linda Vitoria; Monawati Monawati; Fauzi Fauzi (Universitas Syiah Kuala, 2021)
The teaching and learning activities at schools and universities have been affected by the Covid-19 pandemic. This article was aimed at describing teachers’ point of view on the implementation of distance learning at PGSD FKIP Unsyiah, especially in mathematics courses. The participants were 3 mathematics teachers at PGSD FKIP Unsyiah. Data was collected through interview and analyzed qualitatively. Results showed that the preparation of learning depended on the completeness of materials uploaded to the university elearning website; courses were conducted using zoom, Whatsapp, elearning website and Youtube channel; evaluation was conducted by giving tasks to the students; lack of IT skills and unstable internet connection were among the obstacles in distance learning. This study implies that the implementation of distance learning could be optimized by overcoming the obstacles.